2008
DOI: 10.1016/j.phytochem.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Plant bioactives for ruminant health and productivity

Abstract: Plants have been used throughout history for their medicinal properties. This use has often focused on human health but plants have also been, and still are, applied in ethnoveterinary practice and animal health management.In recent times, the use of synthetic chemicals has become prevalent. Public awareness of the potential environmental and health risks associated with heavy chemical use has also increased. This has put pressure on regulatory bodies to reduce the use of chemicals in agriculture. The most str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
140
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(153 citation statements)
references
References 99 publications
2
140
0
11
Order By: Relevance
“…Some plants, mainly dicotyledonous plants including most of the legumes, produce secondary metabolites, of which some are bioactive on intake and in the rumen environment (Barry and McNabb, 1999;Rochfort et al, 2008). According to their nature and concentration in the diet, they can provide nutritional and environmental advantages or disadvantages.…”
Section: Effects Of Secondary Metabolites On Digestion and Intakementioning
confidence: 99%
“…Some plants, mainly dicotyledonous plants including most of the legumes, produce secondary metabolites, of which some are bioactive on intake and in the rumen environment (Barry and McNabb, 1999;Rochfort et al, 2008). According to their nature and concentration in the diet, they can provide nutritional and environmental advantages or disadvantages.…”
Section: Effects Of Secondary Metabolites On Digestion and Intakementioning
confidence: 99%
“…Physiologically, these substances have osmotic regulatory properties and can act as a methyl group donor 3 . Among these mesoionic-type substances, trigonelline ( Figure 1) is somewhat unique as it displays hypoglycemic, hypocholesterolemic, antitumoral and anti-septic properties 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of Moringa oleifera performed by Mantur and Kamal 9 using HPLC, different contents (3.55, 2.60, 2.15, 1.90 and 1.60 mg·g -1 ) were found in the pods, leaves, roots, stems and flowers, respectively. Many analytical techniques were employed for the characterization and identification of trigonelline 3,9 . Machado et al 10 observed by NMR spectroscopy a content of 1.20 mg·g -1 of trigonelline in Coffea Arabica roots.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of tannins in legumes on protein degradation, resulting from tannin-protein binding and 68 precipitation, has been described in many publications (Karnezos et al, 1994;Koivisto and Lane, 2001) 69 and were also reviewed by Mueller-Harvey (2006) and Rochfort et al (2008). Tannin-protein binding may 70 increase the nutritive value of the forage for ruminants by an increase in rumen escape proteins which can 71 subsequently be released at the low abomasal pH (Oh and Hoff, 1987) for absorption in the small intestine 72 (Thomson et al, 1970;Jones and Mangan, 1977).…”
Section: Introduction 41mentioning
confidence: 99%